Penggunaan Polipirrol Sebagai Matriks Dalam Sintesis Bahan Komposit Elektrokromik Prussian Blue# - Fitrilawati Fitrilawati; Rustam Efendi Siregar; May On Tjia (Jurnal Matematika & Sains, 1997)
Polypyrrole (PPY) and Prussian blue (PB) are well known electrochromic materials having different ranges of electrochromicity and recycleability. In order to study the possibility of optimizing theirs properties, composites of PPY-PB have been synthesized by means of electrochemical process. The results of synthesis are characterized by cyclic voltammogram, UV-Visible spectroscopy and infrared measurements. The analysis of data indicates good electrochromic contrast of the composite film and significant enhancement of recycleability. Further enhancement of recycleability of PPY-PB composites could still be expected by optimization of PPY/PB composition in the composites.